PENGEMBANGAN E MODUL MEMBACA PERMULAAN UNTUK ANAK USIA 5 – 6 TAHUN - Suhati Suhati; Indri Astuti (Institut Pendidikan Tapanuli Selatan, 2023)
This research is a research development or Research and Development (R&D) which aims to develop the E Module for Beginning Reading for Children aged 5-6 Years with the ADDIE development model. This research took place in TK Negeri 1 Sandai with 30 participants. This pre-reading e module has a novelty value, namely the e-module designation that targets Kindergarten students aged 5-6 years so that it is adapted to the characteristics of students. In this pre-reading e module, students are invited to learn to recognize letters by applying the steps to reading this beginning, equipped with interesting animated pictures to foster interest in reading and enthusiasm for learning in students. The results of the study indicate that the achievement of students' initial reading skills can be seen in the final assessment of 4.77 (95%) with Very Good Developing criteria (BSB). while in the initial assessment, namely 2.51 (50.2%) the criteria began to develop (MB). The achievement of the final assessment showed a significant difference between the results of the initial and final assessment, namely 2.26 (45.2%). The final assessment showed that the participants' basic reading ability increased by 45.2% compared to the initial assessment before using the e-module reading beginning. Thus, it can be concluded that the use of E Beginning Reading Module for Children aged 5-6 Years is very effective to use